Corruption v Democracy - part one: Capturing the South African State - Lewis, David (New Agenda: SA Journal of Social and Economic Policy, 2024)
Does corruption undermine democracy? Does democracy constrain corruption? Is democracy a necessary condition for successfully combatting corruption? These questions were initially posed from the intensely practical perspective of a non-governmental organisation (NGO) dedicated to combatting corruption. And so, reformulated from that perspective I ask: is it necessary to actively promote democracy in order to combat corruption? Or conversely, does the current global decline in the quality of national democracies compromise the fight against corruption?